PENGEMBANGAN PRODUKSI KERAJINAN SEBAGAI UPAYA MENDUKUNG PROGRAM PENGENTASAN KEMISKINAN - Maisaroh, Siti (Semarang State University, 2008)
The research is aimed at finding the dominan factors do develop the small-scale industry as an effortto the poor program to empower the society. By using the methodology participation action researh(PAR) involving the active participation of the society, Especially to the small craftsment to clarify theproblems and how find the solution. The collecting is done by using the method of simple randomsampling against 100 respondents sample of the small-scale industrial housholds. The result of thesurvey shows that skill factor and the marketing factor belong to the core variable. Which each of themhas the higest elasticity against the product to the amount of 0.4147 or 41,47% and 0.2517 or 25,17%.Accordingly, the recomendation to develop the small-scale industry as reflected on the increasingproduct, it is hoped to give priority to the skill factor and marketing factor then to the capital factor orother factor.Keywords: skill, marketing and capital factor to develop the small craftsment solution.